2020
DOI: 10.1086/709479
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Rate Interacts with Resource Availability to Determine Individual Variation in Microhabitat Use in the Wild

Abstract: Ecological pressures such as competition can lead individuals within a population to partition resources or habitats, but the underlying intrinsic mechanisms that determine an individual's resource use are not well understood. Here we show that an individual's own energy demand and associated competitive ability influence its resource use, but only when food is more limiting. We tested whether intraspecific variation in metabolic rate leads to microhabitat partitioning among juvenile Atlantic salmon (Salmo sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 96 publications
(124 reference statements)
1
42
0
Order By: Relevance
“…Metabolic rate is thought to be an integrative measure of energy use and ecological interactions (Brown et al, 2004). For example, standard metabolic rate in Atlantic salmon (Salmo salar) influenced habitat choice and was related to resource access (Auer et al, 2020). We therefore expected to find links between oxygen consumption and morphology, movement, and foraging in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic rate is thought to be an integrative measure of energy use and ecological interactions (Brown et al, 2004). For example, standard metabolic rate in Atlantic salmon (Salmo salar) influenced habitat choice and was related to resource access (Auer et al, 2020). We therefore expected to find links between oxygen consumption and morphology, movement, and foraging in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in metabolic rate can also underlie differences in foraging, swimming ability and behavioural traits such as dominance, aggression and risk-behaviours ( Metcalfe et al , 2015 ). It is difficult, however, to assess whether the reduced RMR observed in numerous treatments at the alevin stage and in fry that experienced chronic developmental stressors would be beneficial or harmful to later life stages because the effects of changes in metabolic rate can be highly context dependent in terms of the habitat, food availability and temperatures present ( Reid et al , 2012 ; Auer et al , 2018 ). Additionally, metabolic performance can vary depending on the measurement temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Vgll3 genotype has been shown to have a strong effect on salmon life-history (Ayllon et al, 2015;Barson et al, 2015;Verta et al, 2020), and recent findings have suggested that this effect might be mediated by vgll3-induced differences in body condition (Debes et al, 2021). Taking this together with the connections between standard metabolic rate (SMR) and resource acquisition and assimilation (Armstrong et al, 2011;Auer, Bassar, et al, 2020;Auer, Solowey, et al, 2020;Bochdansky et al, 2005;Millidine et al, 2009;Rosenfeld et al, 2015), we hypothesized that vgll3 genotype might be asserting some of its effects through changes in energetic physiology that would be reflected in SMR. However, we did not detect any difference in either SMR or body condition between juvenile Atlantic salmon individuals of different homozygous vgll3 genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic phenotype is a multi-faceted set of traits, covering not just standard metabolic rate, but also the maximum metabolic rate, aerobic scope, and daily energy expenditure, to mention some. Additionally, the consequences of variation in metabolic traits are context-dependent and may change under different environmental conditions and life stages (Auer, Bassar, et al, 2020;Auer, Solowey, et al, 2020;Bochdansky et al, 2005;Millidine et al, 2009;Norin & Metcalfe, 2019). We initially planned to also measure metabolic rate under exhaustive swimming to obtain data on maximum metabolic rate (MMR), but had to abandon these trials as we were unable to motivate juvenile salmon of this age and size to do any exhaustive swimming, either by swim tunnel or by hand chasing.…”
Section: Discussionmentioning
confidence: 99%